1998
DOI: 10.1128/aac.42.8.1878
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Lipoprotein Distribution of Liposomal Nystatin Is Influenced by Protein Content of High-Density Lipoproteins

Abstract: The plasma lipoprotein distribution of free nystatin (Nys) and liposomal nystatin (L-Nys) in human plasma samples with various lipoprotein lipid and protein concentrations and compositions was investigated. To assess the lipoprotein distributions of Nys and L-Nys, human plasma was incubated with Nys and L-Nys (equivalent to 20 μg/ml) for 5 min at 37°C. The plasma was subsequently partitioned into its lipoprotein and lipoprotein-deficient plasma fractions by step-gradient ultracentrifugation, and each fraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…8,18 This rationale is further substantiated by recent findings which demonstrated that as the amount of HDL protein decreased, the percent of nystatin recovered within the HDL fraction proportionally decreased following the incubation of liposomal nystatin. 19 The studies presented in this paper determine the plasma lipoprotein distribution of AmpB and ABLC following incubation in plasma from different human subjects with varying total and lipoprotein lipid concentrations and address the role of lipoprotein lipid and protein content on the distribution of AmpB to plasma lipoproteins.…”
Section: Introductionmentioning
confidence: 99%
“…8,18 This rationale is further substantiated by recent findings which demonstrated that as the amount of HDL protein decreased, the percent of nystatin recovered within the HDL fraction proportionally decreased following the incubation of liposomal nystatin. 19 The studies presented in this paper determine the plasma lipoprotein distribution of AmpB and ABLC following incubation in plasma from different human subjects with varying total and lipoprotein lipid concentrations and address the role of lipoprotein lipid and protein content on the distribution of AmpB to plasma lipoproteins.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism for brevetoxin uptake under these conditions is also consistent with the passive diffusion of cholesterol. Certain drugs show a preference for HDL among the lipoproteins; however, this may be due to the high protein:lipid ratio of HDL (Cassidy et al 1998; Kennedy and Wasan 1999; Wasan et al 1997). Further studies will be needed with brevetoxins to determine the degree of selectivity for the toxin to the different lipoprotein classes, with particular reference to lipoprotein profiles representative of human plasma.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested that a different mechanism which was not influenced by the lipoprotein mass determined the plasma distribution of liposomal nystatin. Further studies are required for clarification of this issue [122,134].…”
Section: Plasma Distribution Of Liposomal Nystatin Differs From That mentioning
confidence: 97%